Paying the circadian toll: The circadian response to LPS injection is dependent on the Toll-like receptor 4 - Paladino, Natalia (2010)
Systemic low doses of the endotoxin lipopolysaccharide (LPS) administered at CT15 (circadian time 12 corresponds to locomotor activity onset) induce phase delays of locomotor activity rhythms in mice. To evaluate if this effect was mediated by the Toll-like receptor 4 (TLR4), our present aim was to characterize the circadian behavior and LPS-induced circadian response of TLR4 (LPS receptor)-deficient mice (in C57bl/10 and C3H backgrounds). In mutants, we observed a free-running period and a light-induced phase delay similar to the one observed in their corresponding wild-type (WT) littermates. The LPS-induced phase delay, wheel running inhibition and c-Fos/Per-1 immunoreactivity in the paraventricular nuclei observed in WT mice was absent or significantly decreased in the TLR4-deficient mice. In conclusion, we show that LPS-induced circadian responses are mediated by TLR4.